Alfabetismo científico y educación - Cabral Perdomo, Ignacio (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 2001)
We are living in an era of great changes as for the progress, but at the same time it is full of contradictions, where many citizens perceive science and technology as something that has nothing to do with their lives. Therefore the author asks himself important questions, such as how to increase the interest for science or how to reduce the lack of scientific knowledge. He draws some interesting conclusions that concern not only teachers, but also student and other social agents.